Barriers and Solutions to the Adoption of Digital Therapeutics from the Perspectives of Stakeholders - BADLEY, Harriet (2020)
Despite the promising increase in the adoption of digital health products in the UK health market, global adoption of digital therapeutics is relatively low. The adoption of digital therapeutics by users and the healthcare system could present a number of benefits. To understand the barriers causing low adoption, and to produce potential solutions to overcome these barriers, 10 interviewees from different stakeholder groups are interviewed. The research project finds a number of potential barriers causing low adoption such as poor infrastructure, lack of awareness, poor understanding, insufficient government policy. In order to address these barriers, the projects suggests possible solutions and recommendations.